Movement, activity and hunting behaviour of leopards in the Cederberg mountains, South Africa. (1st February 2013) - Martins, Quinton; Harris, Stephen
Abstract: Few data are available on the behaviour of leopards in the absence of competing large predators and human impact, both of which are believed to influence leopard activity and movements. Remote camera traps and global positioning system (GPS) collars were used to quantify leopard activity in the Cederberg Mountains, seasonal and sexual differences in their movements, and determine whether nocturnal hunting success was related to lunar activity. Seventy‐seven per cent of camera‐trap photographs were at night, with a strong male bias (69%) in captures. Daily displacement using one location per day suggested that males moved significantly further than females. However, multiple locations (≥6 per day) showed no difference because males moved in a more linear fashion, but not further each day, than females. In the Cederberg Mountains, an open rocky habitat with low human impact and no competing predators, leopards were predominantly nocturnal, mainly hunting diurnal prey species. Hunting success was low: leopards travelled long distances between kills, with nocturnal hunting success higher on darker nights.